Manajemen Pendidikan: Perencanaan dan Evaluasi Dalam Manajemen Pendidikan Dasar dan Menengah - Nuriya, Intan Tirza (Maliki Interdisciplinary Journal, 2025)
Quality education focuses not only on academic knowledge but also on character building and skills development, equipping students to face future challenges. This article emphasizes the importance of effective educational management through the synergy between planning and evaluation in primary and secondary education. Strategic educational planning involves formulating the school’s vision, mission, and goals, accompanied by key implementation steps such as needs analysis, program development, and resource allocation. Meanwhile, evaluation acts as a tool to measure the effectiveness and efficiency of programs and serves as a reflection for continuous improvement. The article also addresses challenges in implementing planning and evaluation, such as budget constraints, insufficient managerial training, and resistance to change. Proposed solutions include improving school leaders’ and teachers’ competencies through training, utilizing technology to facilitate evaluation processes, and fostering a reflective culture within schools. Through the synergy between planning and evaluation, educational management can become more effective and responsive to the needs of students and society. The integration of academic and spiritual values in education is highlighted to ensure that graduates excel intellectually and possess noble character. This study offers a holistic perspective on the critical role of planning and evaluation in educational management to achieve sustainable and relevant educational quality in line with evolving societal demands.